Opportunities for the use of natural and preformed physical factors in the complex treatment of patients with chronic viral hepatitis C with associated non-alcoholic fatty liver disease - Izha, Аnna (Journal of Education, Health and Sport, 2019)
One of the urgent problems of modern hepatology remains the treatment of patients with chronic viral hepatitis C, which is associated with an increase in the incidence and development of complications - cirrhosis of the liver and hepatocellular carcinoma. The presence of non-alcoholic fatty liver disease in patients accelerates the progression rate of HCV infection and reduces the effectiveness and tolerability of antiviral therapy. The above circumstances initiated us to the search for new non-drug technologies for the treatment of this category of patients. The work aimed to evaluate the effectiveness of the integrated use of standard antiviral therapy, drinking silicon low-mineralized sodium bicarbonate mineral water, and EHF-therapy in patients with chronic viral hepatitis C with concomitant non-alcoholic fatty liver disease. We used the following methods: anamnestic, general clinical, biochemical, serological, immunological, Ultrasonographic examination of the digestive organs. We examined 42 patients who were divided into two groups. The control group (22 people) received the basic treatment complex, which included dietary nutrition, standard antiviral therapy for 12 months, and an internal intake of mineral water during the first month of treatment. The main group (20 people), in addition to the basic complex of treatment, additionally received EHF-therapy procedures for three months. Evaluation of the effectiveness of treatment was carried out after 1 and 3 months from the start of treatment. The treatment was accompanied by the positive dynamics of most signs of the disease in both groups, with a predominance of EHF-therapy. In patients of main group, the disappearance of complications of antiviral therapy was established - the absence of cytopenic syndrome, normalization of immunological status, stimulation of interferonogenesis, restoration of equilibrium in the lipid peroxidation system and antioxidant system. These positive results made it possible to complete the course of therapy for all patients and obtain a virological response in 50% of patients.